Bank Competition and Entrepreneurial Gaps: Evidence from Bank Deregulation - Li, Xiang (Journal of Financial and Quantitative Analysis, 2026)
I analyze the effects of bank competition on gender and racial gaps in entrepreneurship. By leveraging interstate bank deregulation from 1994 to 2021, I find that stronger bank competition increases the quantity and quality of banking services offered to minority borrowers. Developing a novel measure of discrimination using narrative information in the complaints filed with the Consumer Financial Protection Bureau, I demonstrate that bank competition reduces discrimination, alleviating the financial constraints of female and minority entrepreneurs. Stronger bank competition also reduces gender and racial gaps in firm performance and business equity accumulation, promoting wealth equality and fostering equitable economic growth.